2020
DOI: 10.3390/ijms21207510
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin-1 Deficiency Decreases Epileptic Activity in Mice

Abstract: Objective: Pannexin-1 (Panx1) is suspected of having a critical role in modulating neuronal excitability and acute neurological insults. Herein, we assess the changes in behavioral and electrophysiological markers of excitability associated with Panx1 via three distinct models of epilepsy. Methods Control and Panx1 knockout C57Bl/6 mice of both sexes were monitored for their behavioral and electrographic responses to seizure-generating stimuli in three epilepsy models—(1) systemic injection of pentylenetetrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 53 publications
(57 reference statements)
2
25
0
Order By: Relevance
“…Such interpretation agrees with our previous studies showing that deletion or blockade of Panx1 improves seizure scores (Santiago et al, 2011). Similarly, Panx1 blockade or deletion reduced the duration of afterdischarges and prevented electrical kindling as well as reduced seizure severity and death following systemic PTZ administration (Aquilino et al, 2020).…”
Section: Role Of Panx1 In Seizures Evidence That Panx1 Plays a Role supporting
confidence: 92%
See 2 more Smart Citations
“…Such interpretation agrees with our previous studies showing that deletion or blockade of Panx1 improves seizure scores (Santiago et al, 2011). Similarly, Panx1 blockade or deletion reduced the duration of afterdischarges and prevented electrical kindling as well as reduced seizure severity and death following systemic PTZ administration (Aquilino et al, 2020).…”
Section: Role Of Panx1 In Seizures Evidence That Panx1 Plays a Role supporting
confidence: 92%
“…showing that Panx1 is upregulated in rodent and human epileptic tissues (Jiang et al, 2013;Li et al, 2017;Mylvaganam et al, 2014;Mylvaganam et al, 2010) and that deletion or blockade of Panx1 attenuates KA-and PTZ-convulsant effects (Aquilino et al, 2020;Dossi et al, 2018;Santiago et al, 2011). In contrast, however, Panx1 activation has been shown to attenuate hyperexcitability under hypoglycemic condition (Kawamura et al, 2010;Kawamura et al, 2014) and to decrease seizure susceptibility in the pilocarpine model (Kim and Kang, 2011).…”
Section: Role Of Panx1 In Seizures Evidence That Panx1 Plays a Role mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that these channels are activated under pathological conditions such as epilepsy and regulate neuronal excitability [ 586 , 592 , 593 , 594 , 595 ]. Pannexin-1 expression seems raised in animal seizure models and in resected human epileptic brain tissue, suggesting relevance to epilepsy [ 586 , 596 , 597 , 598 , 599 ].…”
Section: Other Potential Therapeutic Targets To Considermentioning
confidence: 99%
“…Recently, it was reported that pannexin-1 channel activation promotes seizure generation and maintenance through adenosine triphosphate signaling via purinergic 2 receptors [ 600 ]. Genetic or pharmacological targeting of pannexin-1 channels have anticonvulsant effects in epilepsy models [ 595 , 600 ]. These results suggest that pannexin-1 channel inhibition might represent an alternative therapeutic strategy for treating not only epilepsy but also drug-resistant epilepsy.…”
Section: Other Potential Therapeutic Targets To Considermentioning
confidence: 99%